Sequences of toddler negative emotion and parent–toddler verbal communication during a waking day. (17th September 2019) - Fields‐Olivieri, Margaret A.; Cole, Pamela M.
Abstract: Although the second year of life is characterized by dramatic changes in expressive language and by increases in negative emotion expression, verbal communication and emotional communication are often studied separately. With a sample of twenty‐five one‐year‐olds (12–23 months), we used Language Environment Analysis (LENA; Xu, Yapanel, & Gray, 2009, Reliability of the LENA™ language environment analysis system in young children's natural home environment . LENA Foundation) to audio‐record and quantify parent–toddler communication, including toddlers' vocal negative emotion expressions, across a full waking day. Using a multilevel extension of lag‐sequential analysis, we investigated whether parents are differentially responsive to toddlers' negative emotion expressions compared to their verbal or preverbal vocalizations, and we examined the effects of parents' verbal responses on toddlers' subsequent communicative behavior. Toddlers' negative emotions were less likely than their vocalizations to be followed by parent speech. However, when negative emotions were followed by parent speech, toddlers were most likely to vocalize next. Post hoc analyses suggest that older toddlers and toddlers with higher language abilities were more likely to shift from negative emotion to verbal or preverbal vocalization following parent response. Implications of the results for understanding the parent–toddler communication processes that support both emotional development and verbal development are discussed.